Social Identity, Diversity, Equity, and Inclusion (DEI) in Asian Organizations: Implications for Human Resource Management - Waqar Akbar Khan; Hind El Atmani (The Indonesian Institute of Science and Technology Research, 2026)
Diversity, Equity, and Inclusion (DEI) has become a prominent agenda in human resource management (HRM), particularly in Asian organizations experiencing increasing workforce diversity. However, DEI initiatives often remain symbolic, resulting in tokenism rather than meaningful inclusion. This study employs a conceptual review approach grounded in Social Identity Theory and in-group–out-group bias to analyze DEI implementation in Asian organizational contexts. Drawing on recent empirical and theoretical studies, this paper examines how social identity dynamics influence recruitment, promotion, anti-discrimination policies, and diversity management. The findings suggest that deeply embedded cultural norms, high power distance, and collectivist orientations in Asia intensify social categorization processes, leading to resistance toward superficial DEI practices. This paper contributes to HRM literature by proposing a socially grounded perspective on DEI internalization and offering implications for strategic HRM in Asia.